KAJIAN POLA KONSUMSI DAN STATUS GIZI ATLET DI PUSAT PEMBINAAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) PROVINSI NUSA TENGGARA TIMUR TAHUN 2009 - Nurhasanah Wongso; Aspatria, Utma; Lada, Christina Olly (Jurnal Pangan Gizi dan Kesehatan, 2010)
The aim of this research was to study the consumption pattern and nutrient status of student-athletes in Center of Construction and Sport Practice at Province East Nusa Tenggara. The method of research was a survey method with cross-sectional design study. The research was done in the Center of Construction and Sport Practice for student East Nusa Tenggara Province at Oebufu, from October 2009 until January 2010. Using census, there were 30 athletes had been interviewed. The results showed that the pattern of consumption of athletes was (1) frequency of eating third times a day and snack once a day in the evening, (2) variety of food consumption was classified as good with 7-8 types of food/day, weekly 8-10 types and monthly more than 10 types. The energy sufficiency level of athletes on the average were 73,37% which included insufficient category, which spread in boxing 78,15% (sufficient level), athletics 66,92% (under level), traditional self-defence arts 75,37% (sufficient level), and rattan plaited into a rough ball 65,59% (under level). While the mean of protein sufficiency level of athletes were 64,06% which in under category, which spread in boxing 69,38% (under level), athletics 57,61% (very low level)